The Effect of Using Podcast on Students’ Speaking Skill - Nur Aminah Tanjung; Nurhafni Siregar; Teguh Satria Amin; Yugi Diraga Prawiyata (STKIP Taman Siswa Bima, 2025)
This research purpose to find out whether there is an effect on using podcast as a technique on students’ speaking skill at eleven grade of senior high school of Dwi Tunggal in academic year 2024/2025. This research is quasi experimental research. It involvet 50 students’ of two groups, class X1 MIPA-XI 1 as experimental group and MIPA-XI 2 as control group. The experimental group taught by podcast project meanwhile control group taught by conventional method. The data were gained by using pre-test and post-test. The pre-test was given to both groups before the treatment meanwhile the post-test was given after the treatment for experimental group. The data of pre-test and post-test of both groups were analyzed by descriptive and inferential statistics. The data were counted by uisng SPSS for windows. After data were tested then found unnormal data, the researcher changed the test to be Wilcoxon test. The result of the research showed that there is an effect on the students’ speaking skill of the students who were taught by using podcast in project speaking. In Wilcoxon test, it can be seen that wilcoxon indexof experimentalgroup is 16,71 meanwhile control group is 0, after that Z-value of experimental group (3.721) is smaller than controlgroup (15.740). P-value (Sig. 2-Tailed) of experimental group is ,001. Ha accepted meanwhile Ho rejected, it is mean that there is an effect of using podcast on the students’ speaking skill. In conclusion, the research titled the effect of using podcast on students’ speaking skill has an effect for students’ speaking skill.